2004
DOI: 10.1002/cphc.200400218
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Oscillation and Ultrafast Internal Conversion of Tetrafluoroethene after Excitation at 197 nm

Abstract: C2F4 was excited by using a 150 fs pulse in its longest-wavelength band to the Rydberg (3 s) state and then probed by photoionization techniques at 810 nm. The molecule relaxes in two consecutive steps (time constants 29 and 118 fs), probably via the pipi* state, which is lowered in energy by stretching and twisting the C=C bond. A coherent oscillation (350 fs) was found, which we assign to an overtone of the twist vibration (47.6 cm(-1)) in this state. we also conclude that dissociation to singlet and some tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…It is worth noting that the molecule with one-sided pyramidalization has an electron distribution (Figure 2b) that is zwitterionic and correlates in planar geometry with the 2A g state with two π electrons excited to π*, as already pointed out in ref (16). …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It is worth noting that the molecule with one-sided pyramidalization has an electron distribution (Figure 2b) that is zwitterionic and correlates in planar geometry with the 2A g state with two π electrons excited to π*, as already pointed out in ref (16). …”
Section: Discussionsupporting
confidence: 71%
“…It was argued in ref (16) that recombination of two CF 2 molecules should be easiest if one of them points with its filled nσ orbital to the empty pπ orbital of the other. Hence, the dissociation path will change from pure CC stretch to include also pyramidalization (Figure 2b), and the potential should be lowered in energy in the direction of q 7 (the coordinate of ν 7 ) and/or q 8 .…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism has been used to explain the ultrafast decay of the π 3s Rydberg state of cyclohexene and other molecules. [21][22][23] In tetramethylethylene, the π 3s decay rate at the longest wavelength (232.4 nm) is much slower than in dimethyl-and trimethylethylene. Ab initio computation shows that there is likely an increased energy barrier to accessing the π 3s/ππ* MECI region and, therefore-the fast channel through CI region being closed-leads to a much slower decay.…”
Section: B Non-radiative Decay Processesmentioning
confidence: 99%
“…This mechanism was also used to explain the ultrafast decay of the 3s state of a few other systems. 22,23 The coupling of the V and Rydberg states has been discussed in a number of previous studies. [24][25][26][27][28][29] In the simulation of the ethylene absorption spectrum, Martinez and co-workers found that the coupling of the π 3s Rydberg state with the V state had to been taken into account in order to reproduce the experimentally observed doublet-like structure.…”
Section: Introductionmentioning
confidence: 99%
“…The previous interpretation [119] invoked the positively charged core of the Rydberg state. This has, however, two drawbacks: (1) in solution (where carbenes are also formed) the Rydberg admixture disappears (is shifted to higher energies), leaving only the ps* part, (2) it was shown by ultrafast spectroscopy that the path from the Rydberg state merges into the pp* potential (ethylene: [72], methylated ethylenes: [73], cyclohexene: [65], norbornene: [71], tetrafluoroethylene: [126]). The momentum mechanism was already mentioned in some of these works [65,71,72].…”
Section: Predistortion By Momenta Generated In Preceding Statesmentioning
confidence: 99%